A PILOT STUDY OF DIETARY INTAKE IN CHILDREN - Mariana Dimova-Gabrovska; Desislava Dimitrova; Mariela Deliverska (Peytchinski Publishing, 2018)
Adequate and balanced import of essential nutrients is of particular importance for the developing child's organism. The purpose of the present study was to examine the intake of main macronutrients (proteins, carbohydrates, fats) from the daily diets of children aged 3 - 15 years. Material and methods: Subjects of the study were 45 children at the average age of 7 ± 2.73 years. Based on children and parents' data, 24-hour dietary registers were obtained for all studied children. The data on received food and fluids from the registers were analyzed, and the daily energy intake values (E%) of proteins, carbohydrates and fats were derived. Results: For all studied children, mean values of protein intake of 15.8 ± 3.5 E%, fat intake of 38.1 ± 7.5 E% and carbohydrate intake of 49.5 ± 7.31 E% were found. Conclusion: The study results show that protein and carbohydrate intake values are consistent with the physiological norms for the age, while the fat intake values are above the recommended in our young patients.